Peran Maktabah MUI Sumatera Utara dalam Mendukung Kajian Al-Qur’an dan Tafsir - Agusman Damanik; Miftahul Jannah; Aisyah Nurul Aini; Ikhtiari Ikhtiari; M. Ihsan; Nurpadila Nurpadila (Pusat Riset dan Inovasi Nasional, 2024)
Maktabah, as an institution providing Islamic information, plays an important role in supporting the development of Qur'an studies and tafsir. This article aims to examine the contribution of the Maktabah of the Indonesian Ulema Council of North Sumatra in facilitating scientific activities related to the Qur'an and interpretation through the provision of collection materials, services, and institutional assistance. This research applies a qualitative approach with a literature study method equipped with a descriptive analysis of the function of maktabah as an Islamic reference center. Data were obtained from institutional documents, collection catalogs, and supporting literature relevant to the development of Qur'an studies. The findings of the study revealed that maktabah functions as a forum for scientific documentation, a channel for the dissemination of interpretive knowledge, and a tool to increase Qur'an literacy for academics and the wider community. In addition, the maktabah also supports discussions, seminars, and research activities based on classical and contemporary texts, thereby strengthening the Islamic scientific tradition at the regional level. The existence of maktabah also contributes to building a literacy culture based on authoritative sources and encourages integration between textual and contextual studies in understanding the Qur'an. These findings highlight the urgency of improving management, digitizing services, strengthening human resources, and expanding the collection of maktabah to meet the demands of Qur'an study and interpretation in a sustainable manner in the modern era.